The Association of Environmental Changes and the Replacement of Mosquito Fauna in the Colombo District, Sri Lanka - Priyangika, B.A.S.; De Silva, B.G.D.N.K.; Jayatunga-Katuwawalage, D.P.W. (Department of Forestry and Environmental Science University of Sri Jayewardenepura, 2014)
A mosquito survey was carried out for 8 months between October 2009 and May 2010 in 12 randomly selected urban (6) and semi-urban (6) areas in the Colombo District of Sri Lanka. Thirty eight mosquito species were identified from which Anopheles interruptus, An. pseudojamesii, Aedes stevensoni, Ae. edwardsi, Ae. vittatus, Culex barraudi, Cx. fatigans, Cx. univittatus, Cx. aculeatus, Cx. purplexus, Cx. spiculosus, Cx. quadripalpis, Cx. halifaxi, Uranotaenia atra, Ur. unguiculata were new findings that were not recorded during a previous survey conducted in 1981-1982 in the same locations. Rainfall had a direct relationship (p=0.000) with the distribution and the density of mosquitoes. Unplanned urbanization, anthropogenic activities and irregular or non-disposal of domestic waste products may have led to population replacement of the mosquito fauna in these locations.
Keywords: environmental changes, mosquito fauna, Sri Lanka